Clinical characteristics, diagnostic modalities, and therapeutic strategies of spontaneous renal artery dissection: A systematic review and diagnostic analysis - Jiahao Zhu; Zengqiang Xu; Yang Geng; Mengxin Jiang; Chang Xu; Yingjiang Xu (PLoS ONE, 2026)
Objective To investigate the clinical features, diagnostic approaches, and treatment strategies of spontaneous renal artery dissection (SRAD) through systematic review and data analysis, thereby providing evidence-based insights for optimizing clinical management. Methods A systematic search was conducted across PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), and Wanfang Database. Case-control studies, cohort studies, and case series were included. Demographic data, symptomatology, diagnostic modalities, treatment regimens, and clinical outcomes were extracted. Statistical analyses were performed using RStudio. Results A total of 73 case reports involving 97 patients were included. The mean patient age was 46 years, with a male predominance (82.5%, 80/97). The most common presenting symptom was acute-onset flank pain (74.2%), and comorbid hypertension was observed in 61.9% of cases. Computed tomography angiography (CTA) was the primary diagnostic modality (85.6%), with multimodal imaging utilized in 87.6% of cases. Revascularization rates differed significantly between conservative management (37.1%), endovascular intervention (71.0%), and surgical intervention (6.2%) (P < 0.01). Regarding blood pressure outcomes: the proportion of patients achieving normotension without medication was significantly higher in the non-conservative group (54.1%, 20/37) than in the conservative group (30.0%, 6/20) (P < 0.05); however, there was no statistically significant disparity in the overall blood pressure control rate (normotension without medication + controlled with medication) between groups (P > 0.05). Overall mortality was 3.1%, and renal function deterioration occurred in 30.9% of patients. Conclusion Management of SRAD necessitates individualized decision-making. Conservative therapy remains appropriate for most patients, while endovascular intervention demonstrates superior revascularization efficacy in cases with severe symptomatology or dissection progression. Prospective studies are warranted to validate therapeutic disparities and establish standardized diagnostic and treatment protocols.